Imaging Nanomedicine-Based Drug Delivery: a Review of Clinical Studies - Man, Francis; Lammers, Twan; T. M. de Rosales, Rafael (Molecular imaging and biology, 2018)
Imaging plays a key role in the preclinical evaluation of nanomedicine-based drug delivery systems and it has provided important insights into their mechanism of action and therapeutic effect. Its role in supporting the clinical development of nanomedicine products, however, has been less explored. In this review, we summarize clinical studies in which imaging has provided valuable information on the pharmacokinetics, biodistribution, and target site accumulation of nanomedicine-based drug delivery systems. Importantly, these studies provide convincing evidence on the uptake of nanomedicines in tumors, confirming that the enhanced permeability and retention (EPR) effect is a real phenomenon in patients, albeit with fairly high levels of inter- and intraindividual variability. It is gradually becoming clear that imaging is critically important to help address this high heterogeneity. In support of this notion, a decent correlation between nanomedicine uptake in tumors and antitumor efficacy has recently been obtained in two independent studies in patients, exemplifying that image-guided drug delivery can help to pave the way towards individualized and improved nanomedicine therapies.